2008
DOI: 10.1017/s1461145707008334
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroid pregnenolone sulphate inhibits long-term potentiation via activation of α2-adrenoreceptors at excitatory synapses in rat medial prefrontal cortex

Abstract: Pregnenolone sulphate (PREGS) is one of the most important neuroactive steroids. Previous study showed that PREGS enhanced long-term potentiation (LTP) via activation of post-synaptic NMDA receptors at excitatory synapses in the hippocampus. The present paper studied the effect of PREGS on LTP at excitatory synapses in the pyramidal cells of layers V-VI of the medial prefrontal cortex (mPFC) using whole-cell patch-clamp in slices and made a comparison with that in the hippocampus. We also studied the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Therefore, we first examined whether adenylyl cyclase (AC) and PKA were involved in the observed β 1 -adrenergic-dependent inward current. Extracellular application of the AC inhibitor MDL 12330A (20 μM, Wang et al, 2008 ; Zhang et al, 2009 ; Simons et al, 2012 ; Socodato et al, 2017 ) did not affect the amplitude of the dobutamine-dependent inward current. The dobutamine-dependent inward current amplitudes without and in the presence of the inhibitor in the bath were -32.11 ± 4.5 pA (n = 7) and -31.6 ± 2.5 pA (n = 9), respectively ( p = 0.9172, unpaired t-test, Figures 8Aa,b ).…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, we first examined whether adenylyl cyclase (AC) and PKA were involved in the observed β 1 -adrenergic-dependent inward current. Extracellular application of the AC inhibitor MDL 12330A (20 μM, Wang et al, 2008 ; Zhang et al, 2009 ; Simons et al, 2012 ; Socodato et al, 2017 ) did not affect the amplitude of the dobutamine-dependent inward current. The dobutamine-dependent inward current amplitudes without and in the presence of the inhibitor in the bath were -32.11 ± 4.5 pA (n = 7) and -31.6 ± 2.5 pA (n = 9), respectively ( p = 0.9172, unpaired t-test, Figures 8Aa,b ).…”
Section: Resultsmentioning
confidence: 86%
“…Neurosteroids (PREGS) blocks LTP of excitatory synapses in rat medial prefrontal cortex (mPFC) via interaction with α 2 -adrenoreceptors secondary to enhancement of Gi proteins. After treatment of mPFC slices with the α 2 -adrenoreceptor inhibitor “yohimbine,” the blocking effect of PREGS on the induction of LTP was completely inhibited ( 72 ).…”
Section: Effect Of Nassmentioning
confidence: 99%
“…In accordance, blockade of these receptors prevents the induction of LTP (Kemp & Manahan‐Vaughan, 2008; Flores et al 2010). In contrast, the activation of adrenergic α1 and α2 receptors reduces LTP (Mondaca et al 2004; Takamatsu et al 2008; Wang et al 2008), and therefore counteracts the effects of β‐adrenergic receptors on plasticity. With regard to LTD, the effects of β‐adrenergic receptor activation are conflicting: Kemp & Manahan‐Vaughan (2008), as well as Lemon and colleagues (Lemon et al 2009) described an enhancement of LTD, whereas a diminution or prevention was found in other studies (Katsuki et al 1997; Lin et al 2008).…”
mentioning
confidence: 99%